1980
DOI: 10.1093/nar/8.20.4671
|View full text |Cite
|
Sign up to set email alerts
|

Histone 2B can be modified by the attachment of ubiquitin

Abstract: Histone 2B in mouse and man can be modified by the post-translational addition of ubiquitin. In mouse L1210 cells, both H2B variants are modified, however only to the extent of 1-1.5% compared with about 11% of H2A. Analysis of cyanogen bromide peptides shows that ubiquitin is attached to the C-terminal part of the histone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
144
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(146 citation statements)
references
References 5 publications
2
144
0
Order By: Relevance
“…It is widely distributed in animals, plants, yeasts and bacteria [1,2]. In animal cells ubiquitin has been found both in free form [1,4] or covalently bound by its carboxyl terminal to other proteins [5][6][7][8]. In the chromatin of interphase cells, ~10% of histone 2A and -,-1% of histone 2B are covalently linked to ubiquitin [8].…”
Section: Introduction 2 Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely distributed in animals, plants, yeasts and bacteria [1,2]. In animal cells ubiquitin has been found both in free form [1,4] or covalently bound by its carboxyl terminal to other proteins [5][6][7][8]. In the chromatin of interphase cells, ~10% of histone 2A and -,-1% of histone 2B are covalently linked to ubiquitin [8].…”
Section: Introduction 2 Materials and Methodsmentioning
confidence: 99%
“…In animal cells ubiquitin has been found both in free form [1,4] or covalently bound by its carboxyl terminal to other proteins [5][6][7][8]. In the chromatin of interphase cells, ~10% of histone 2A and -,-1% of histone 2B are covalently linked to ubiquitin [8]. Since the H2A-ubiquitin conjugate, protein A24, is absent from metaphase chromosomes, it has been suggested that ubiquitin plays a role in the cell cycle [9,10].…”
Section: Introduction 2 Materials and Methodsmentioning
confidence: 99%
“…Monoubiquitylated histone H2B: from general to highly specific transcription regulator Ubiquitylation of histone H2B in mammalian cells was identified over three decades ago [37], but more than two decades passed before the function of this modification in regulating mammalian chromatin-associated processes was deciphered. The first breakthrough came with the identification of the budding yeast protein Bre1 [38,39], which, together with the ubiquitin-conjugating enzyme Rad6, serves as the E3 ligase in the monoubiquitylation of the yeast histone H2B on lysine 123 (K123) within transcribed chromatin [38][39][40][41].…”
Section: Open Access Under CC By-nc-nd Licensementioning
confidence: 99%
“…About 5-15 % and 1-2 % of histones H2A and H2B, respectively, are ubiquitinated (Robzyk et al 2000;West and Bonner 1980). Histones H3 and H1 are also targets for ubiquitination, but the abundance of ubiquitination marks in these histones is low (Chen et al 1998;Pham and Sauer 2000).…”
Section: Ubiquitination and Sumoylation Of Histonesmentioning
confidence: 99%